Menganalisis Nilai IHSG Beserta Faktor-Faktor Yang Mempengaruhi Di Era Pandemik Covid-19 - Halwa Annisa Khoiri; Emylia Arghawaty (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2020)
The Covid 19 caused instability in the Indonesian economic. One of the benchmarks is fluctuations of IHSG which dropped significantly when the PSBB began to take effect. According to the previous research, fluctuations of IHSG were influenced by the price of gold, the exchange rate of the IDR against the USD, and the Dow Jones Industrial Average (DJIA). The data used in this research are daily data during the Covid 19 in Indonesia from March to June. The results obtained that all of these factors significantly influence the fluctuation of IHSG. By using four factors, it is able to explain the variation of IHSG fluctuation of 63.9%.